PENGARUH KOMPETENSI DAN PENEMPATAN TERHADAP KINERJA KARYAWAN PT. ALAM SUTERA REALTY TBK - Ella Siti Chaeriah (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
Increasing competency in supporting the success of employees achieving the target of work provided is an important factor and is supported by the suitability of existing job requirements. This study aims to analyze the simultaneous and partial influence of competence and placement on the performance of employees at PT. Alam Sutera Realty Tbk involving 74 employees. The results of the study show that there are positive effects both simultaneously and partially on competence and placement on the performance of employees at PT. Alam Sutera Realty Tbk.